Study on physiological changes and response mechanism of Cerasus humilis under alkali stress - Pan, Meitong; Jiang, Shan; Ma, Lengleng; Ma, Junbai; Yue, Chenzhuo; Kong, Lingyang; Wang, Danli; Ma, Wei; Liu, Xiubo; Ren, Weichao (Frontiers in Plant Science, 2025)
IntroductionCerasus humilis has high economic and nutritional value, but at the molecular level, there are few studies on salt-alkali stress of C. humilis, and no one has reported the response mechanism of the oxidation system of C. humilis under abiotic stress.Methods and resultsIn this research, transcriptomic and metabolomic analysis showed that C. humilis had a wide range of metabolic activities under alkali stress, and antioxidant enzymes played an important role in response to alkali stress. ChWRKY29 and ChWRKY34, which are likely to respond to alkali stress, were screened based on transcriptomic data and phylogenetic relationship, and their direct regulation on downstream ChMSD2 and ChCSD2 genes were verified by yeast single hybridization experiment. Combined with heat map and qPCR analysis, ChWRKY29 and ChWRKY34 may regulate the up-regulation of ChMSD2 and ChCSD2 gene expression under alkali treatment, and further affect the antioxidant capacity of plants in response to alkali stress. The analysis of ChSOD gene family showed that 9 ChSODs were identified from C. humilis, which were the closest relatives to Pyrus bretschneideri. There are a certain number of cis-acting elements in the ChSOD promoter region for hormone and abiotic stress, and there is no tandem replication between ChSOD genes, but only one fragment replication. Fragment repetition may be the main driving force for the evolution of SOD gene family in C. humilis, and the results of interspecific collinearity analysis indicate that C. humilis and Malus pumila are most closely related.DiscussionIn this study, the mechanism of alkali resistance of C. humilis was discussed, which provided reference for exploring the mechanism of alkali resistance of rosaceae, in order to provide scientific theoretical basis for expanding the cultivation range and development and utilization of C. humilis.